An absolute approach to using whole exome DNA and RNA workflow for cancer biomarker testing - Malhotra, Richa; Javle, Vyomesh; Tanwar, Nishtha; Gowda, Pooja; Varghese, Linu; K, Anju; Madhusudhan, Nandhitha; Jaiswal, Nupur; K. S., Bhargavi; Chatterjee, Manjima; Prabhash, Kumar; Sreekanthreddy, Peddagangannagari; et al. (Frontiers in Oncology, 2023)
The concept of personalized medicine in cancer has emerged rapidly with the advancement of genome sequencing and identification of clinically relevant variants that contribute to disease prognosis and facilitates targeted therapy options. Whole Exome Sequencing (WES) remains a gold standard for the investigation of tumor mutation profile and genome-wide signatures that help in clinical management. In this study, we propose to validate a whole exome-based tumor molecular profiling for DNA and RNA from formalin-fixed paraffin embedded (FFPE) tumor tissue. The study included 166 patients across 17 different cancer types. The scope of this study includes identification of Single Nucleotide Variants (SNVs), Insertions/Deletions (InDels), Copy Number Alterations (CNAs), Gene Fusions, Tumor Mutational Burden (TMB), and Microsatellite Instability (MSI). The assay yielded a mean read depth of 150-250X, with >80% of on-target reads and a mean uniformity >90%. Clinical maturation of WES (DNA&RNA) based assay was achieved by analytical and clinical validation for all the types of genomic alterations in multiple cancers. We here demonstrate an LOD of 5% for SNVs and 10% for InDels with 97.5% specificity, 100% sensitivity, and 100% reproducibility. The results were >98% concordant with other orthogonal techniques and appeared to be more robust and comprehensive in detecting all the clinically relevant alterations. Our study demonstrates the clinical utility of exome-based approach of Comprehensive Genomic Profiling (CGP) for cancer patients at diagnosis and disease progression. The assay provides a consolidated picture of tumor heterogeneity, prognostic and predictive biomarkers, thus helps in putting precision oncology in practice.